CYBERSECURITY RISKS MANAGEMENT OF INDUSTRIAL CONTROL SYSTEMS: A REVIEW - Shikhaliyev, Ramiz H. (Institute of Information Technology, Ministry of Science and Education of the Republic of Azerbaijan, 2024)
Industrial control systems (ICS) form the basis of critical infrastructures, managing complex processes in various sectors of industry, energy, etc. With the increasing frequency and complexity of cyber threats, effective management of ICS cybersecurity risks is critical. This paper is devoted to the analysis of approaches used in the field of cybersecurity risk management of automated process control systems. The study examines the cybersecurity risks of ICS and the role of international standards in managing cybersecurity risks. The results of the analysis carried out in this paper can serve as information for the development of new reliable cybersecurity risk management systems for ICS.